Corporate Criminal Liability in Criminal Acts on The Position in an Automotive Company - Zulfita Zahra (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract Corporate Criminal Liability concerns the issue of liability, intentionality or negligence of the Corporation. The cases of consumers’ money embezzlement occuring in Automotive Companies in Indonesia are frequently not submitted to court. Although there were some cases that had been submitted in court and had obtained permanent legal force, the trapped party was only the members or company’. Meanwhile, the company has never been charged. This is because the Indonesia Criminal Code does not recognize legal subjects in corporation. In contrast, Criminal Code only recognizes human as subject to criminal law (Article 59 of the Criminal Code). In addition, the absence of strict regulation regulation provided on Liability of Business Actors (Company/Corporation) against consumers’ losses as stipulated in Act No. 8 of 1999 concerning Consumer Protection (UUPK), specifically the losses from the legal action of employees of the company and senior company officers, is also a leading factor for the development of criminal acts in corporations. The element of examining corporate as the subject to criminal acts miscunduct is difficult to implement due to its non-human nature. However, if the corporation is not demanded to provide liability just because of the difficulty of proving perpetration, impunity to corporation will occur. Keywords: Criminal Act; Corporate Criminal Liability; Penal System